PANDANGAN SYAFI’IYAH TENTANG KEENGGANAN UNTUK MENIKAH PADA WANITA DEWASA (STUDI KASUS DI DESA NYALINDUNG KECAMATAN CIPATAT KABUPATEN BANDUNG BARAT) - Rofi Risti fauziawati; Abdullah Afif (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Islam encourages its followers to get married, as a form of obedience to Allah SWT. Although marriage is encouraged, in Nyalindung Village there is still an adult woman who is reluctant/postponing getting married. This reluctance triggers curiosity and opens questions: What are the factors behind this reluctance, and what is the view of Syafi'iyah regarding the factors that motivate the reluctance to marry an adult woman. This research is descriptive qualitative research using field or empirical studies. The author in obtaining data uses three data collection techniques, namely interviews, observation, and documentation. Meanwhile, the analysis used is data reduction, exposure and conclusion techniques. Based on the results of field research, the factors that cause adult women to be reluctant to marry are: trauma (psychological) factor, the factor of feeling happy without marriage and wanting to focus on career, and the factor of wanting to take care of parents. If in Syafi'iyah, the law of marriage for women who are reluctant to marry for the reasons above is makruh.